The Effect of Perceived Value on Repurchase Intention of Mcdonald's Products When Carrying Out Palestine Washing Mediated By Purchase Attitude And Word of Mouth - Murthy, Kavita Krishna; Lindiawati, Lindiawati (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the significant positive influence of perceived value on purchase intention on McDonald's products mediated by purchase attitude and word of mouth as a link between perceived value and purchase intention. This research design uses a quantitative approach in the form of a questionnaire. A total of 322 respondents responded to this questionnaire in Indonesia using a questionnaire that applies a Likert scale of 1-5. Data were selected using purposive sampling techniques, then analyzed with WarPLS. This study measures perceived value, word of mouth, and purchase attitude as well as purchase intention towards the product after conducting Palestine Washing. This study has 2 paths, namely direct and indirect paths in influencing purchase intention. The role of purchase attitude and word of mouth is a full mediation of the relationship between perceived value and their intention to buy McDonald's products after conducting Palestine Washing. This study refers to previous studies, which show that the relationship between perceived value towards McDonald's products and their intention to buy the product is direct and indirect. Purchase intention can be indirect due to the mediation of purchase attitude and word of mouth to have an influence from perceived value to purchase intention